Critical Care Intern Nurses Stressors and Their Management Strategies - Sameh Ali Altaybani, Masouda Hassan Abd El-Hamid, Mohamed Ezz El Regal Abo Saba (International Journal of Innovative Research in Medical Science, 2017)
Nursing has been identified as a stressful occupation. The transition from a student to new graduate can be stressful and ''is a reality shock''. Novice nurses have specific stressors that might be different from other nurses and today they feel that they are most frustrated by the lack of care and concern of others. Therefore, this study was conducted. Aim of the study: to identify the critical care intern nurse stressors and their management strategies. Design: descriptive research design was used to conduct this study. Settings: Intensive care units of Alexandria Main University Hospital (Casualty Care Unit and General Intensive Care Unit) and health insurance hospital. Methods: The subject of the study consisted of all critical care intern nurses working in all above mentioned settings at the study time (80 nurses). Two tools were used to collect the data: Tool I : intern nurse stressors questionnaire and Tool II: intern nurse stress management questionnaire tool. Results: This result indicated that intern nurses perceived high to extreme level of stress. Among the three stress subscales; work management was perceived as the extreme level of stress followed by interpersonal relationships, and workload. Self-control was the most common management strategy of stress used by intern nurses. Conclusion: high stress is prevalent among intern nurses. Major stressors of interns were related to work management, followed by interpersonal relationship and workload. Intern nurses are coping with their stressors by self-control and cognitive strategies.